Twenty questions from the surgeon to the radiologist to better plan an open partial horizontal laryngectomy - Crosetti, Erika; Succo, Giovanni; Sapino, Silvia; Bertotto, Ilaria; Cirillo, Stefano; Petracchini, Massimo; Fondello, Gabriele; Arrigoni, Giulia; Tascone, Martina; Piazza, Cesare; Farina, Davide; Ravanelli, Marco (Frontiers in Oncology, 2024)
Open partial horizontal laryngectomies (OPHLs) represent a valuable therapeutic option for tumors of the intermediate T-category and, in selected cases, for locally advanced tumors with low-volume extra-laryngeal extension. The eligibility of patients treated with this type of surgery has increased with the introduction of the modular approach to OPHL planning. This strategy follows the introduction of the classification proposed by the European Laryngological Society, based on the extent of horizontal resection. Optimization of the selection is the result of a meticulous work-up process involving close cooperation between experienced surgeons and radiologists, followed by final quality control by pathologists. Computed tomography and magnetic resonance imaging are study methods whose pearls and pitfalls are well known, especially when performed at a high level of expertise. In this paper, based on the experience of two high-volume centers, a checklist of 20 questions addressed by the surgeon to the radiologist before planning an OPHL was proposed. Considerations regarding case selection are reported for each of the questioned parameters. A very simple question-and-answer process is easy to understand and mainly addressed by less experienced colleagues who wish to increase their knowledge and skills in performing this type of surgery.